Education, Training, and Prevention of Sports Injuries for Teachers and Sports Coaches: A Simulation-Based Approach at SDN Kamasan 1 - Masnur Ali; Nofi Marlina Siregar; Eka Fitri Novita Sari; Novri Asri (International Journal of Public Devotion, 2026)
This community service activity aims to educate and improve the understanding and skills of physical education teachers and sports coaches in preventing and managing sports injuries in elementary school settings. The participants consisted of 25 individuals, including physical education teachers and sports coaches from the vicinity of SDN Kamasan 1. Participatory Rural Appraisal, demonstrations of prevention techniques, and hands-on training in initial injury management through case simulations. Evaluations were conducted before and after the training to measure improvements in participants’ knowledge and skills. The results showed an increase in participants’ understanding of injury prevention and care, from 68% in the pretest to 85% in the posttest. Additionally, 90% of participants were able to correctly perform first aid techniques, up from 72% in the pretest. A total of 95% of participants stated that this training was very beneficial and relevant for application in school sports activities. This initiative successfully enhanced the preparedness of teachers and coaches in creating a safe sports environment for students.Edukasi Pelatihan Pencegahan dan Perawatan Cedera Kepada Guru dan Pelatih Olahraga: Pendekatan Simulasi di SDN Kamasan 1ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk mengedukasi dan meningkatkan pemahaman dan keterampilan guru serta pelatih olahraga dalam mencegah dan menangani cedera olahraga di lingkungan sekolah dasar. Subjek kegiatan terdiri dari 25 peserta, yang meliputi guru pendidikan jasmani dan pelatih olahraga di sekitaran SDN Kamasan 1. Metode pelaksanaan meliputi penyuluhan materi cedera olahraga, demonstrasi teknik pencegahan, serta pelatihan langsung penanganan awal cedera melalui simulasi kasus. Evaluasi dilakukan sebelum dan sesudah pelatihan untuk mengukur peningkatan pengetahuan dan keterampilan peserta. Hasil menunjukkan adanya peningkatan pemahaman peserta terhadap pencegahan dan perawatan cedera Pretest 58% dan Posttest 87%. Selain itu, 90% peserta mampu mempraktikkan teknik pertolongan pertama dengan benar dari pretest 72%. Sebanyak 95% peserta menyatakan pelatihan ini sangat bermanfaat dan relevan untuk diterapkan dalam kegiatan olahraga sekolah. Kegiatan ini berhasil meningkatkan kesiapsiagaan guru dan pelatih dalam menciptakan lingkungan olahraga yang aman bagi siswa.Kata Kunci:Pelatihan; cedera olahraga; guru olahraga; pertolongan pertama; pencegahan cedera